2012
DOI: 10.4238/2012.september.10.5
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous abscisic acid increases antioxidant enzymes and related gene expression in pepper (Capsicum annuum) leaves subjected to chilling stress

Abstract: ABSTRACT. To elucidate how physiological and biochemical mechanisms of chilling stress are regulated by abscisic acid (ABA) pretreatment, pepper variety (cv. 'P70') seedlings were pretreated with 0.57 mM ABA for 72 h and then subjected to chilling stress at 10°/6°C (day/night). Chilling stress caused severe necrotic lesions on the leaves and increased malondialdehyde and H 2 O 2 levels. Activities of monodehydroascorbate reductase (DHAR), dehydroascorbate reductase, glutathione reductase, guaiacol peroxidase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 38 publications
15
72
0
Order By: Relevance
“…This finding is in full agreement with Guo et al (2012), who found that ABA significantly alleviated the effect of chilling stress-induced leaf damage in pepper. These results indicated that pretreatment with ABA can effectively alleviate the damage from LTS in 'Sultana' grapevine.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in full agreement with Guo et al (2012), who found that ABA significantly alleviated the effect of chilling stress-induced leaf damage in pepper. These results indicated that pretreatment with ABA can effectively alleviate the damage from LTS in 'Sultana' grapevine.…”
Section: Discussionsupporting
confidence: 93%
“…Under LTS, ABA has a close interaction with cell biomembrane phospholipids to preserve their integrity and normal function (Guschina et al 2002). Moreover, it plays a role in alleviating oxidative damages by increasing the activity of ROS scavenging enzymes (Jiang and Zhang 2004;Guo et al 2012). It is possible that exogenous ABA may induce plant metabolic defense responses directly (such as increase in soluble carbohydrate, proline and phenolic compounds) and indirectly (through ROS) and improve the integrity of the cell membrane and FT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies implicate exogenous ABA treatment in increased plant tolerance to abiotic stresses such as chilling and osmotic stress (Jiang and Zhang, 2002;Guo et al, 2012;Ozfidan et al, 2012), but ABA is often implicated as a suppressor of plant resistance (Curvers et al, 2010). The mechanism underlying this disparity between plant responses to biotic and abiotic stress responses is unclear.…”
Section: ) Wrky33 Suppresses Downstream Target Genes Nced3mentioning
confidence: 99%
“…In pepper, for example, the germination is affected for temperature stresses (Guo et al, 2012). Since the experiment was conducted in controlled environment, the response found was due the genotypic differences.…”
Section: Discussionmentioning
confidence: 99%